TINGKAT SUKU BUNGA, DEBT TO EQUITY RATIO, DAN EARNING PER SHARE PENGARUHNYA TERHADAP RETURN SAHAM PERUSAHAAN YANG TERDAFTAR PADA INDEK LQ-45 DI BURSA EFEK INDONESIA - Gusti Ayu Mahanavami; Uday Gunawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
This study aims to determine the effect of interest rates, Debt to equity ratio (DER), and Earning per share (EPS) on stock returns of companies listed on the LQ-45 index on the Indonesia stock exchange period 2015-2017.Samples were taken using a purposive sampling method. The population in thisstudy is companiesregistered in the LQ-45 index for the 2015-2017 period. The total population in this study was 45 companies. From a population of 45 companies, 5 companies were obtained as samples of the study with an observation period of 3 years. Data were analyzed using multiple linear regression analysis.Based on the results of data analysis, it was concluded that the interest rate had a negative and significant effect on stock returns so that the first hypothesis was accepted. DER has a positive and significant effect on stock returns so that the second hypothesis is rejected. EPS has a negative and insignificant effect on stock returnsso that the third hypothesisisrejected.